(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2021)
The drastic modification of the educational landscape due to social emergencies such as the COVID-19 pandemic disturbs the flow of educational processes, which is detrimental to the well-being of the educator and the learner. As classes resumed for AY 2020-2021 despite clamors for an academic freeze, the experiences shared in classes, and the monitoring of outputs by instructors prompted the researchers to advance this study to obtain concrete feedback on the conduct of remote learning in the School of Business Sciences of Union Christian College. The descriptive research design was utilized to ascertain the status of student experiences in the synchronous and asynchronous classes and determine whether significant differences occur with the interplay of various profile variables. 126 SBS students voluntarily responded to the survey from July to September 2021. The main data gathering tool of the study was adopted from a validated survey questionnaire by the UCC’s Center for Research Development, Extension, Productivity, and Service-learning. Adherence to the Institutional ERB was observed during the study period. Meanwhile, descriptive and inferential statistics were used to treat the gathered data. The result of the study indicated that more of the respondents are aged 17-19, mostly female with a declared family income of PhP10,000.00 and below; more are freshman and BS Accountancy students. In terms of their experiences in synchronous and asynchronous learning, the respondents indicated that they were encouraged by the family, peer and social support (highest), and teacher/school support they felt but were restrained by their capability to manage distance learning (lowest), technological resource learning support, and coping techniques. In terms of differences in these areas as determined by the profile variables, the younger respondents felt family, peer, and social support significantly better than the older respondents. The sophomores felt the teacher and school support significantly better than the junior respondents. The rest of the profile variables were not determinants of the respondents’ experiences in synchronous and asynchronous learning. Based on the findings, it is concluded that SBS students need further support to enable them to be well-adjusted in any variety of learning modalities by providing avenues for them to gain better personal capabilities in managing to learn and in their coping mechanisms and to sustain further the support they receive from their families, peers, teachers, and school. Meanwhile, outsourcing can aid students with difficulty in technological learning support.